TEGANGAN PERTUMBUHAN PERMUKAAN KAYU JABON UMUR 5 TAHUN DARI HUTAN RAKYAT DI SLEMAN, YOGYAKARTA - Ridho, Muhammad Rosyid; Marsoem, Sri Nugroho; Listyanto, Tomy; Sulistyo, Joko (Universitas Tanjungpura, 2024)
Burflower (Neolamarckia cadamba Miq.) is a fast-growing wood species which has been planted in some community forest on Java Island in recent years. This study aims to examine the surface growth stress of 5-year-old burflower wood from a community forest in Sleman, Yogyakarta. In addition, the axial variation of the surface growth stress within the stem also studied. The strain gauges method was conducted to determine the surface-released strains (SRS) in the stem periphery. The results show that the mean value of longitudinal SRS was -241,58 Î¼É› (-239